Implementation of Islamic Religious Education at the LKSA Princess Aisyiyah Orphanage Babat Challenges and Solutions - Ainun Jariyah; Sulalah; M. Fahim Tharaba; Ika Khaironi (Institut Agama Islam Negeri Pontianak, 2026)
The formation of social character in foster children at child welfare institutions is a crucial aspect of the educational and caregiving process, particularly in instilling empathy, responsibility, mutual aid, and social interaction skills. In this context, etiquette education and parenting styles are two factors hypothesized to be related to the formation of social character in foster children at the Aisyiyah Babat LKSA. This study aims to determine the relationship between etiquette education and parenting styles with the social character of foster children, both partially and simultaneously. This study employs a quantitative approach using a correlational research design. The population and sample consist of 50 respondents using a saturation sampling technique. Data collection was conducted through the distribution of questionnaires, which were then analyzed using multiple linear regression with the aid of SPSS through descriptive statistical tests, classical assumption tests, partial tests (t-tests), simultaneous tests (F-tests), and the coefficient of determination. The results of the study indicate that, partially, the variable of adab education has a significant relationship with the social character of foster children, with a calculated t-value of 2.503 > table t-value of 2.011 and a significance level of 0.016 < 0.05. Meanwhile, the parenting style variable does not have a significant relationship when analyzed partially, with a calculated t-value of 0.915 < the critical t-value of 2.011 and a p-value of 0.365 > 0.05. Simultaneously, both variables have a significant relationship with social character, with a calculated F-value of 3.908 > table F-value of 3.20 and a significance level of 0.027 < 0.05. The R-Square value of 0.143 indicates a contribution of 14.3%. From these research results, it can be concluded that character education and parenting styles are related to the formation of the social character of foster children.